A Noninvasive Metabolic Syndrome Model Using an Extremely Small Minipig, the Microminipig - Takehiro Yamaguchi; Takanori Yamazaki; Hiroaki Kawaguchi; Masashi Tawa; Yasuhiro Nakamura; Masayuki Shiota; Mayuko Osada-Oka; Akihide Tanimoto; Tomio Okamura; Katsuyuki Miura; Hiroshi Iwao; Minoru Yoshiyama; et al. (Elsevier, 2014)
Abstract.: Metabolic syndrome (MetS) induces serious complications; therefore, we developed a noninvasive MetS model using an extremely small minipig, the Microminipig. For 8 weeks, Microminipigs were administrated a high-fat and high-cholesterol diet (HFCD) for atherosclerosis and NG-nitro-l-arginine methyl ester (l-NAME) for inhibiting nitric oxide synthase. HFCD significantly increased serum low-density lipoprotein levels, l-NAME increased blood pressure and cardiac hypertrophy, and HFCD-induced aortal arteriosclerosis was accelerated by l-NAME administration. Endothelium-dependent relaxation of the coronary artery was remarkably decreased by l-NAME administration. This model may be useful for elucidating the mechanisms of MetS and developing new therapeutic medicines for its treatment. Keywords:: metabolic syndrome, Microminipig, nitric oxide